PERBANDINGAN PUISI INDONESIA â€œKARAWANG-BEKASIâ€ KARYA CHAIRIL ANWAR DAN PUISI SPANYOL â€œMI ULTIMO ADIOSâ€ KARYA JOSÃ‰ RIZAL - Monica, Laura; Fitriyani, Dwi; Indriyani, Dewi; Raissa Zahara, Sella (Reduplikasi: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2023)
The aim of this research article is to obtain results of a literary comparison of the poem entitled "Karawang-Bekasi" by Chairil Anwar with the Spanish poem "Mi Ultimo Adios" by JosÃ© Rizal. This article describes the aspects and meaning of poetry contained in the poem entitled "Karawang-Bekasi" by Chairil Anwar with the Spanish poem "Mi Ultimo Adios" by JosÃ© Rizal. This research uses descriptive research methods with note-taking data collection techniques. The results obtained in this research article include personification, metaphor, litotes, rhetoric, repetition, allegory, euphemism, ellipsis, allieration and litotes. Then the difference lies in the meaning of the poem where the poem Mi Ultimo Adios by Jose Rizal tells about the death sentence imposed on him on charges of rebellion. He rebelled against the colonialists, in this case the Spanish, to defend his country, the Philippines. Meanwhile, the poem Karawang-Bekasi by Chairil Anwar contains the story of the death of heroes on the battlefield that occurred in the cities of Karawang and Bekasi.